Browsing Interaction Events in Recordings of Small Group Activities via Multimedia Operators - Martins, Diogo S.; Pimentel, Maria da Graça C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The recording of multimedia sessions of small group activities, such as meetings, lectures and webconferences, is becoming increasingly popular following the improvements in recording technologies, the popularity of web-based media repositories, and the opportunity of reviewing or sharing the activity in a later moment. When reviewing a (potentially long) multimedia session, a user may not be interested in watching it linearly as a whole, but only on browsing or skimming specific fragments of interest. For tackling this requirement, the literature reports the opportunity of indexing interaction events that typically occur in these activities, such as slide transitions, speech turns and gestures. In this paper we investigate the issue of combining different types of interaction events as an aid to navigate in multimedia sessions. First, we define temporal interval-based composition operators so that the semantics of groups of annotations can be orchestrated in queries. Second, we demonstrate the operators in a web-based multimedia player that enable users to browse a multimedia session with the aid of visualizations and filters over interaction-focused annotations. In order to experiment with the model, we report a case study with multimedia information recorded by a capture environment in use.